DISCOVERING STRATEGIES OF STUDENT IN ENHANCING ENGLISH SPEAKING FLUENCY: A CASE STUDY AT SIXTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM AT ISLAMIC UNIVERSITY OF INDRAGIRI TEMBILAHAN - Alwi Hafis; Syafrizal; Sri Erma Purwanti (Program Studi Pendidikan Bahasa Inggris, 2026)
This study aims to explore the strategies used by sixth-semester students of the English Study Program at the Islamic University of Indragiri Tembilahan to enhance their speaking fluency in English. Speaking fluency is a crucial skill in foreign language learning, yet many students still face difficulties due to a lack of practice, anxiety, low confidence, and an unsupportive language environment. This research employed a qualitative method with a case study design. Data were collected through interviews and questionnaires, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that students employed a variety of learning strategies classified into cognitive, metacognitive, and socio-affective strategies, based on the frameworks of O'Malley & Chamot (1990) and Oxford (1990). Cognitive strategies such as practicing, rehearsal, and summarizing were the most frequently used. Metacognitive strategies like planning and self-monitoring also played a significant role. Socio-affective strategies such as self-encouragement and interaction with peers helped reduce anxiety and increase confidence. These strategies were chosen based on students’ individual learning preferences, motivation, and their need to improve real-time communication skills. This study suggests that lecturers should understand and support the use of these strategies in order to design more effective teaching methods to enhance students’ speaking fluency.